Advanced numerical modelling of friction stir welded low alloy steel. (August 2018) - Ahmad, Bilal; Galloway, Alexander; Toumpis, Athanasios
Graphical abstract: Highlights: The Coupled Eulerian Lagrangian approach has been used to model the friction stir welding of steel grade DH36. Use of temperature dependent DH36 properties enabled more accurate behaviour of the whole welding process. The results of two models with diverse rotational and traversing speeds were discussed. The heat-affected zone in the slow weld model was larger than the fast weld model in all processing stages. Major flash was observed on the surface of the slow weld model workpiece. Abstract: The development of advanced joining processes such as friction stir welding (FSW) is necessary to maintain manufacturing competitiveness in any industrial nation. Substantial research that has been carried out on FSW of aluminium alloys has demonstrated considerable benefits; this has led to greater interest in FSW of steel and other high melting temperature alloys. In this context, numerical modelling can provide cost-effective development of steel FSW. Due to the limitations associated with the Johnson Cook model when employed in high melting temperature metals, a three-dimensional thermo-mechanical simulation of FSW featuring low alloy steel with previously generated experimental temperature dependant properties has been successfully solved in Abaqus/Explicit. Unlike any previous research in which either the workpiece is assumed as a high viscous body or the tool is modelled as a moving heating source, the Coupled Eulerian Lagrangian approach has been innovatively applied to model the FSW process on steel. All stages of FSW (plunge, dwell and traverse) have been modelled for slow and fast process parameters and their results compared with previous experimental work on the same grade of steel. In each model, the weld shape and weld surface flash were found to be in exceptionally close alignment with previous experimental results.